2007
DOI: 10.1248/bpb.30.379
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase 1B Inhibitory Activity of Amentoflavone and Its Cellular Effect on Tyrosine Phosphorylation of Insulin Receptors

Abstract: Insulin binding to the insulin receptor (IR) results in autophosphorylation on specific tyrosine residues, which in turn further activates the receptor tyrosine kinase and provides binding sites for the recruitment and subsequent phosphorylation of signaling proteins such as insulin receptor substrate (IRS) 1-4.2,3) Phosphorylated IRS activate several signaling cascades that mediate the biological effects of insulin including glucose uptake and glycogen synthesis. 2,3)Protein tyrosine phosphatases (PTPs) catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Our recent studies demonstrated that the flavonoids are the prominent active biochemical compound of Selaginella tamariscina. Amentoflavone is one of the main flavonoids from Selaginella tamariscina and it has been reported that amentoflavone is a non-competitive inhibitor of PTP1B (Na et al, 2007), which can interact with and dephosphorylate activated IR as well as IRS proteins (Johnson et al, 2002;Asante-Appiah and Kennedy, 2003). Its overexpression has been shown to inhibit the IR signaling cascade and increased expression of PTP1B occurs in insulin-resistant states (Ahmad et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies demonstrated that the flavonoids are the prominent active biochemical compound of Selaginella tamariscina. Amentoflavone is one of the main flavonoids from Selaginella tamariscina and it has been reported that amentoflavone is a non-competitive inhibitor of PTP1B (Na et al, 2007), which can interact with and dephosphorylate activated IR as well as IRS proteins (Johnson et al, 2002;Asante-Appiah and Kennedy, 2003). Its overexpression has been shown to inhibit the IR signaling cascade and increased expression of PTP1B occurs in insulin-resistant states (Ahmad et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Phaseollin 107 was synthesized by Mohamed et al in 1987 [64] (Figure 4). From the MeOH extract of plant Selaginella tamariscina, used to treat infectious disease and malignant tumors, amentoflavone 115 was obtained and characterized as a noncompetitive PTP1B inhibitor (IC 50 value of 7.3±0.5 μmol/L and K i value of 5.2 μmol/L) [65] . Treatment with 115 of 32D cells overexpressing the IR resulted in a dose-dependent increase in tyrosine phosphorylation of IR, possibly through inhibition of PTP1B to enhance insulin-induced intracellular signaling.…”
Section: Flavonoidsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Previously, we found that an EtOAcsoluble extract of the root bark of Erythrina mildbraedii exhibited inhibitory effect on PTP1B activity and demonstrated that prenylated flavonoids are principles of this extract. 14) Further study on the EtOAc-soluble extract of E. mildbraedii led to the isolation of three new (1-3) and three known (4-6) prenylated flavonoids.…”
mentioning
confidence: 99%